2021
DOI: 10.1002/smsc.202100069
|View full text |Cite
|
Sign up to set email alerts
|

High‐Efficient and Dosage‐Controllable Intracellular Cargo Delivery through Electrochemical Metal–Organic Hybrid Nanogates

Abstract: Intracellular cargo delivery plays an important role in fundamental biological research [1] and therapeutic medical applications, [2] ranging from intracellular function analysis, [3] gene encoding for cellular reprogramming, [4] and the inhibition of gene expression inside cells. [5] Cargo delivery requires safe and efficient access to cells and different intracellular locations such as the nucleus and mitochondria due to impermeable outer cell membranes, including small molecules, [6] nucleic acid genes, [7]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
0
8
1
Order By: Relevance
“…The flux values were 0.133 nmol s –1 cm –2 for the 380 nm NTs and 0.219 nmol s –1 cm –2 for the 750 nm NTs. These values were higher than those obtained with LOx enzymes but lower than the results with green fluorescence protein (GFP, 25 kDa) at 0.8 mM . We observed that the protein flow rate through the NTs stamp was more influenced by concentration than by molecular weight relative to the diffusion constant.…”
Section: Resultscontrasting
confidence: 72%
“…The flux values were 0.133 nmol s –1 cm –2 for the 380 nm NTs and 0.219 nmol s –1 cm –2 for the 750 nm NTs. These values were higher than those obtained with LOx enzymes but lower than the results with green fluorescence protein (GFP, 25 kDa) at 0.8 mM . We observed that the protein flow rate through the NTs stamp was more influenced by concentration than by molecular weight relative to the diffusion constant.…”
Section: Resultscontrasting
confidence: 72%
“…Moreover, hollow nanostructures and electroporation are beneficial for trans‐barrier transportation because they can transport multifunctional loads into adherent cells. [ 176 ] By combining nanoparticles with external forces such as mechanical, electrical, and photothermal perforation, excellent intracellular delivery techniques can be developed to improve delivery efficiency and dose controllability.…”
Section: Application Prospects Of Homs‐based Ddssmentioning
confidence: 99%
“…[32] Copyright 2021, The Royal Society of Chemistry. Internal stimuli pH-responsive PEG, TEG Inward diffusion [47,100,118,123,126,129] Redox-responsive PEG Inward diffusion [56,136,156] Enzyme-responsive ALG Cross-linking-codependent [14,27,106,124,130,132,158] Electroresponsive PLGA, PEG Inward diffusion [70,146,196] ROS-responsive PEG, PLGA Self-assembled [149,150,160,162,165] External stimuli Thermoresponsive PEG, PLGA In situ formation [7,30,34,42,67,170,171,173,175,17 8,181] Light-responsive PLGA, ALG Self-assembled [9,28,113,183,185] Magnetic-responsive ALG, HA Cross-linking-codependent [29,166,193,194,195] Mechanoresponsive PEG, PCL Inward diffusion [146,148,197,199,200] Ultrasound-responsive PEG Inward diffusion [14,163,201,…”
Section: Ph-responsive Nanocomposite Hydrogelsmentioning
confidence: 99%
“…A combination of electroresponsive nanostructures with compound-loaded nanostructures, and electroresponsive nanostructures with electroresponsive compounds can also be used for electroresponsive drug delivery. [157,158] With the use of polyelectrolytes that contain large numbers of ionizable groups, the polymers become responsive to electrical stimulation by shrinking or swelling. We can design an electroresponsive nanocomposite hydrogel to deliver an antitumor drug targeted at specific sites.…”
Section: Electroresponsive Nanocomposite Hydrogelsmentioning
confidence: 99%